Predictive value of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) for all-cause and cardiovascular mortality with non-hyperhomocysteinemia: evidence from NHANES 1999 to 2006 - Deng, Liang; Zhong, Haicheng; Zhou, Sheng; Wang, Ziming; Sun, Jingjing; Liu, Chang; Li, Xinghui; Cheng, Quankai; Deng, Jie (Frontiers in Nutrition, 2025)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) has emerged as a promising biomarker for lipid metabolism, with established links to mortality in various chronic diseases. However, its prognostic value in individuals with non-hyperhomocysteinemia (NHHcy), a population often overlooked in cardiovascular risk assessment, remains unexplored. This study aimed to determine the association between NHHR and all-cause and cardiovascular disease (CVD) mortality and its predictive value among adults with NHHcy.MethodsThis study used the National Health and Nutrition Examination Survey database (1999–2006) and employed the National Death Index to determine mortality outcomes. The relationship between NHHR and mortality was evaluated using restricted cubic splines (RCS) and a multivariable Cox proportional hazards model. The threshold effects were assessed using a piecewise Cox proportional hazards model. Analysis of subgroups, interactions, and survival was done. Lastly, the NHHR's predictive value for mortality as well as its potential mediating effects were evaluated.ResultsA total of 13,847 participants were included in our study. Over the course of the follow-up, there were a total of 2,886 mortality, of which 739 were due to CVD. A “U-shaped” correlation between NHHR and mortality was shown by the RCS. A one-unit rise in NHHR was linked to a 19 and 17.4% decrease in the odds of all-cause and CVD mortality, respectively, when NHHR was below the inflection point; the hazards rose by 6.4 and 11.9%, respectively, when NHHR was over the inflection point. There were interaction effects between several subgroups in the relationship between NHHR and mortality from all-cause and CVD. Additionally, NHHR's area under the curve for predicting death from all-cause and CVD was 0.897 (0.890–0.904) and 0.921 (0.910–0.932), respectively. According to mediation analysis, the association between NHHR and all-cause mortality was mediated by aspartate aminotransferase.ConclusionNHHR was shown to have a “U-shaped” relationship with both all-cause and CVD mortality in the NHHcy population, as well as an excellent mortality predictive value. In the future, NHHR could be used for predicting mortality risk and prognosis in the NHHcy population.